The Dissociation between Polarity, Semantic Orientation, and Emotional Tone as an Early Indicator of Cognitive Impairment - Arias Tapia, Susana A.; Martínez-Tomás, Rafael; Gómez, Héctor F.; Hernández del Salto, Víctor; Sánchez Guerrero, Javier; Mocha-Bonilla, J. A.; Barbosa Corbacho, José; Khan, Azizudin; Chicaiza Redin, Veronica (Frontiers in Computational Neuroscience, 2016)
The present study aims to identify early cognitive impairment through the efficient use of therapies that can improve the quality of daily life and prevent disease progress. We propose a methodology based on the hypothesis that the dissociation between oral semantic expression and the physical expressions, facial gestures, or emotions transmitted in a person's tone of voice is a possible indicator of cognitive impairment. Experiments were carried out with phrases, analyzing the semantics of the message, and the tone of the voice of patients through unstructured interviews in healthy people and patients at an early Alzheimer's stage. The results show that the dissociation in cognitive impairment was an effective indicator, arising from patterns of inconsistency between the analyzed elements. Although the results of our study are encouraging, we believe that further studies are necessary to confirm that this dissociation is a probable indicator of cognitive impairment.